Emerging High‐Level Tigecycline Resistance: Novel Tetracycline Destructases Spread via the Mobile Tet(X) - Fang, Liang‐Xing; Chen, Chong; Cui, Chao‐Yue; Li, Xing‐Ping; Zhang, Yan; Liao, Xiao‐Ping; Sun, Jian; Liu, Ya‐Hong (BioEssays, 2020)
Antibiotic resistance in bacteria has become a great threat to global public health. Tigecycline is a next‐generation tetracycline that is the final line of defense against severe infections by pan‐drug‐resistant bacterial pathogens. Unfortunately, this last‐resort antibiotic has been challenged by the recent emergence of the mobile Tet(X) orthologs that can confer high‐level tigecycline resistance. As it is reviewed here, these novel tetracycline destructases represent a growing threat to the next‐generation tetracyclines, and a basic framework for understanding the molecular epidemiology and resistance mechanisms of them is presented. However, further large‐scale epidemiological and functional studies are urgently needed to better understand the prevalence and dissemination of these newly discovered Tet(X) orthologs among Gram‐negative bacteria in both human and veterinary medicine. The novel mobile tetracycline‐inactivating enzymes, Tet(X3)–Tet(X5), could confer high‐level tigecycline resistance. They have been disseminated in diverse bacterial hosts from a wide range of ecological niches through promiscuous plasmids and ISCR2. This complex dissemination can be driven by selective pressure from the massive use of the early tetracyclines.